IMPLEMENTATION OF THE ZAKAT VILLAGE INDEX 2.0: CASE STUDY OF ANJIR MUARA KOTA VILLAGE, ANJIR MUARA CITY, BARITO KUALA REGENCY - Ahmad Ryan Nugraha; Manik Mutiara Sadewa (ADISAM Publisher, 2025)
This study aims to evaluate the implementation of the Zakat Village Index (ZVI) version 2.0 in Anjir Muara Kota Village, located in Anjir Muara District, Barito Kuala Regency. The assessment focused on five key dimensions: economy, health, education, social and humanitarian affairs, and counseling and advocacy. A mixed-methods approach was employed, using an exploratory sequential design. The study began with qualitative data collection through interviews and observations, followed by quantitative analysis using a gradual weighted index method. The results showed a total ZVI score of 0.68, which falls within the